New Pneumococcal Carriage Acquired in Association with Acute Respiratory Infection Is Prone to Cause Otitis Media - Auranen K; Syrjanen R; Leino T; Kilpi T (PUBLIC LIBRARY SCIENCE, 2022)
For considering vaccine-prevention of pneumococcal acute otitis media (PncAOM), relationships between pneumococcal carriage, respiratory infection and PncAOM need to be understood. We analyzed nasopharyngeal samples collected from 329 unvaccinated Finnish children aged 2-24 months at scheduled visits and at visits during respiratory infection in 1994-97. We assessed temporal associations of respiratory infection with pneumococcal acquisition and whether PncAOM hazard depends on the relative timing of acquisition and the infection onset. The data comprised 607 person-years of risk-time for acquisition, 245 person-months of concurrent respiratory infection and carriage, and 119 episodes of PncAOM. The acquisition hazard was 3-fold in the month preceding respiratory sickness (hazard ratio, HR 3.5, 90% credible interval CI 2.9, 4.1) as compared to acquisition in healthy children. Moreover, the PncAOM hazard was markedly higher (HR 3.7, 90% CI 2.4, 5.3) during the first month of carriage acquired around the acute phase of respiratory infection (between 1 month before and 1 week after the sickness onset), as compared to carriage acquired later during sickness. The high proportion (76%) of PncAOM events occurring within 1 month of acquisition was due to frequent acquisition being associated with respiratory infection as well as the susceptibility of such acquisition to cause otitis media.